RELIGIOUS AND CULTURAL DIALECTICS IN DETERMINING EARLY-AGE MARRIAGE (Case Study of the Increase in Early-age Marriage in Pinrang City from the Maqashid Shariah Perspective) - Bate, Nurdalia; Faiz, ABD Karim; Samin, Sabri; Musyahid, Achmad; Almuhtadi, Ahmad Saiful Haq; Wahidin, Wahidin (istinbath, 2023)
Marriages conducted in Pinrang Regency often do not pay attention to the rules of marriage that have been established, especially the issue of age. Such problems are difficult to avoid, especially in ordinary people, thus reducing the negative impact of early marriage. The role of the National Family Planning Agency through the Office of Population Control, Family Planning, Women's Empowerment, and Child Protection of Pinrang Regency is required. The objectives of this study are as follows: to identify the negative impacts caused by early marriage in Pinrang Regency, to analyze or determine the potential for underage marriage in Pinrang Regency, and to describe the role of the Pinrang Regency government in reducing underage marriage. This study is qualitative research. The approach used is socio-juridical. The research is descriptive qualitative. There are two types of data used, namely primary data and secondary data. The technique of data processing used observation, interviews, documentation, triangulation, and data validity tests using credibility, transferability, dependability, and confirmability. Furthermore, the data analysis technique used the data reduction technique (data reduction), display (data presentation), and conclusion drawing/verification (concluding). Based on the results of this study, it shows that: first, underage marriage has a negative impact, especially concerning health issues. Second, It was found that approximately 90% of underage marriages in Pinrang Regency were conducted by women, with requests for dispensation of marriage being submitted more by people who live in urban areas compared to rural areas. The negative impact presented in early marriage is more dominant than the positive impact. Based on the Maqasyid shari'ah theory, the practice and potential of early marriage in Pinrang City is contrary to Hifdzunnafs for both women and children based on the data that has been described.